Effects of Abstinence Self-Efficacy and Outcome Expectancies of Tobacco Smoking on the Desire to Quit Among Saudi Women: A Cross-Sectional Mediation Analysis. (9th February 2022) - Alanazi, Abdullah M; Almutairi, Shahad F; Alsarami, Alanoud A; Alanazi, Fay J; Alqahtani, Lama H; Alotaibi, Tareq F; Algarni, Saleh S; Monshi, Sarah S; Ismaeil, Taha T
Background: Smoking is one of the major preventable causes of morbidity and mortality and has been associated with numerous illnesses. While smoking is increasing among Saudi women, the characteristics of smoking behavior related to abstinence self-efficacy, which is a belief regarding one's ability to successfully resist performing a behavior, and outcome expectancies, meaning the anticipated consequences of performing a behavior, are unknown. Therefore, this study aimed to test whether abstinence self-efficacy mediated the relationship between tobacco smoking outcome expectancies and the desire to quit tobacco among Saudi women who smoke. Methods: This cross-sectional study collected a sample of 211 Saudi women who smoked tobacco, including cigarettes and shisha. A self-administered questionnaire was used to examine several variables, including abstinence self-efficacy, outcome expectancies, and desire to quit tobacco smoking. Mediational path analysis was used to answer the research question. Indirect effects were estimated through a bootstrapping of 10, 000. Results: All 4 constructs of outcome expectancies (negative consequences, positive reinforcement, negative reinforcement, and appetite/weight control) were associated with lower abstinence self-efficacy and desire to quit tobacco smoking. In the mediation analysis, the indirect effect of negative consequences (standardized beta = −.013, SE = .008, 95% CI [−.030, −.001]), negative reinforcement (standardized beta = −.012, SE = .006, 95% CI [−.025, −.001]), and appetite/weight control (standardized beta = −.008, SE = .006, 95% CI [−.022, −.001]) through abstinence self-efficacy were significant, suggesting mediation in the relationship between outcome expectancies and desire to quit tobacco smoking. Conclusion: Cognitive mechanisms that may explain the desire to quit tobacco smoking among Saudi women were identified. Although future longitudinal studies are required to determine relationships prospectively, targeted interventions that correct tobacco smoking outcome expectancies and boost abstinence self-efficacy skills may reduce tobacco smoking among Saudi women.